Lost in Broadcasting: League of Nations, International Broadcasting and Swiss Neutrality - A. S. Khodnev (Vestnik MGIMO-Universiteta)
The article delves into the historical context of cross-border radio broadcasting during the 1930s by the League of Nations (LN) and the significant impact of Switzerland's neutrality as the host country on this international organization. Drawing from the recently digitized and accessible LN archive in Geneva, this narrative unveils a minor conflict of interest that evolved into a notable political crisis, marking an international legal precedent by showcasing the influence wielded by a smaller host nation upon a global organization. The architects of the League of Nations envisioned Geneva as an ideal hub for the organization's activities, complete with modern communication technologies for global outreach. However, Switzerland's neutral stance posed an obstacle to the establishment of the League's radio broadcasting infrastructure. Recognizing the absence of robust emergency communications, transport links, and the absence of a dedicated radio station in Geneva during the mid-1920s, the LN sought an agreement with the Radio-Swiss station. Consequently, the LN's own radio station, Radio-Nations, commenced broadcasting on February 2, 1932, coinciding with the start of the Conference on the Reduction and Limitation of Arms. By May 1938, amidst mounting tensions in Europe, Switzerland chose to assert complete neutrality within the League. Discussions within the Federal Council revolved around the possibility of suspending the agreement made on May 21, 1930, along with the support for Radio-Nations. Unexpectedly, on November 3, 1938, the LN leadership in Geneva expressed a desire to re-evaluate the 1930 convention. The outbreak of World War II drastically reshaped the relationship between the LN and Radio-Nations. Switzerland decided against entering into a new agreement with the LN, leading to the closure of Radio-Nations on February 2, 1942. Maintaining the nation's neutrality, the Swiss government vigilantly observed the unfolding events during the war. During the peak of Nazi Germany's advances, Bern adopted stringent measures against the LN, upholding a resolute diplomatic stance. However, the Swiss stance toward the LN and the division of Radio-Nations’ ownership gradually shifted from 1943, culminating in the resolution of several financial matters. Ultimately, in 1947, the LN's liquidation commission transferred the remaining assets of Radio-Nations and its radio waves to the United Nations.